Summary of joint guideline on the management of long COVID. Issue 8 (15th September 2021) - Chaplin, Steve
Abstract : NICE, SIGN and the Royal College of General Practitioners have published a joint guideline on identifying and managing the long‐term effects of COVID‐19 ('long COVID') in adults, young people and children. This article summarises the main points of the guidance.